(untitled) (Singaporean Journal of Business Economics and Management, 2014)
Privatization has been proposed as one of the important issues in the many developing countries and particularly Iran. Privatization will follow goals such as reduce the financial burden of the government, increased competition, economic efficiency, increased investments efficiency, optimal use of resources, and etc. Experience has also shown that success not one hundred percent by public companies. So private sector can plays more obvious effect in the policy-making. Considering this and need for attention to importance of the insurer organizations and also increasing complexity, rapid of environmental changes, uncertainty in the organizations’ environment be feel strongly growing need for long-term strategic decisions, and possession of empowerment employees. Hence, if an organization, or in other words, insurer organization be able have available set of employees high-willed, activist and committed to organization and offering organizational citizenship behaviour, could be better have react vulnerable to turbulence competition and threats. One of the philosophies privatization is increased competition and empowerment to different industries including insurance industry. In considering this importance in the this study will be discussed the privatization debate in the insurance industry.